Analysis of Android Malware "Undangan Pernikahan.Apk" Using Static and Dynamic Methods - Muhammad Syafa Asgani; Raphael Bianco Huwae; Andy Hidayat Jatmika (Journal of Computer Science and Informatics Engineering (J-Cosine), 2024)
This research aims to analyze Android malware "UndanganPernikahan.apk" using static methods with reverse engineering techniques and dynamic analysis. The analysis process uses several tools to understand the characteristics, behavior, and impact of the malware after installation on an Android device. The research shows that this malware covertly steals user credentials through several vulnerabilities. The "UndanganPernikahan" malware is a type of spyware disguised as a wedding invitation and runs in the background without the user's knowledge. To avoid similar malware infections, it is recommended to always update the system and applications, only download applications from trusted sources, and conduct digital security training.